Modification of montmorillonite with diamine surfactants - Zaini, Mahirah (2015)
Sodium montmorillonite (Na-MMT) was modified with various type of diamine surfactants. The modification imparts hydrophobic characters of MMT, thus enhancing its compatibility and dispersibility in polymer matrix. In this research, pristine MMT was modified with three types of diamine surfactants, namely, 1,3 diaminopropane (DAP), 1,8 diamino octane (DAO) and 1,5 diamino-2-Methyl pentane (DAMP). These diamines have different molecular structures where DAP has a short linear structure, DAO has eight carbons while DAMP has a methyl branch on its backbone. The modification was carried via cationic exchange process. X-ray diffraction (XRD) analysis showed the enhancement of d-spacing of MMT galleries and the formation of intercalated structure with the incorporation of diamines. Overall, type of diamines did not give significant effect on the d-spacing values with DAMP-MMT exhibited a slightly higher d-spacing at 13. 36 A°. The presence of methyl branch on the DAMP backbone was thought provide more spacing for the diamine to intercalate through the MMT gallery. Meanwhile, the detection of –NH bending amine group at 1470 cm-1 on the Fourier infrared (FTIR) spectra, corresponding to the free surfactant tail, had confirmed the successfulness of cationic exchange reaction between the diamines and MMT surface.